The Development of Art Learning Model at School (A Review of Music Education Learning in Indonesia) - Mack, Dieter (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2015)
At the present time, art education is often ignored. Focus on teaching and learning at school seems to accentuate other subjects, such as: science, economics, and technology. This trend is becoming more concerning for the arts is a field of study, which draws attention to the development of perceptual sensitivity, creativity, as well as social responsibility. However, if art education, in this case is music education, is taught theoretically based on other cultural materials, then the consequences will be worse for students. This study is aimed to draw outlines of music education which hopefully can answer the three aspects of music which are previously described. The outlines are arranged based on recent discoveries in audio perceptions.Â